Valor de la ecografía como predictor de adherencias intrabdominales en gestantes con cesárea previa del Hospital Regional de Loreto – 2022 - Rojas Chavez, Irvin Jhoel (2024)
Intra-abdominal adhesions constitute adverse outcomes frequently reported in different surgical contexts, taking into account that cesarean section is one of the interventions with a significant increase, this has led to the appearance of these complications becoming a health problem, as such In this sense, it is vitally important to explore new strategies that allow a precise characterization of the risk of the appearance of postoperative adhesions. That is why the objective of this research is to determine if ultrasound has value as a predictor of intra- abdominal adhesions in pregnant women with a previous cesarean section at the Regional Hospital of Loreto 2022. A quantitative, observational, analytical, cross-sectional, retrospective study will be carried out. Our research method consists of applying a data collection sheet and then carrying out an analysis that includes descriptive statistics tools such as frequency distribution tables and measures of central tendency and dispersion; e analytical, using chi square; The information collected will be tabulated and the results of the instruments used will be interpreted.